Impact of ERP, Social Media, and CSR on Manufacturing Company Value during COVID-19 - Dwianto, Agus; Setiawati, Erma; Arum S, Nurlita; Hardina, Lulu (PT Larva Wijaya Penerbit, 2023)
This study analyzes the impact of ERP implementation, Instagram usage, and CSR disclosure on the market value of companies in the basic and chemical industries. It focuses on firms listed on the Indonesian Stock Exchange during the COVID-19 pandemic (2020-2022). The results indicate that ERP and Instagram do not significantly affect company value in this sector. However, CSR disclosure has a positive and significant impact on company valuation. Control factors like return on assets and leverage do not significantly influence company valuation during the pandemic.